The Porcupine: An Impartial Style of the Novel - Muhammad Abbas (بازیافت, 2024)
<span style="font-size: 14.0pt; line-height: 115%; font-family: "Jameel Noori Nastaleeq"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In Urdu we can find many a novel relating to political issues. But it is being observed that all of the novelist tries to show their feeling towards any particular political theory or personality. It is necessary to introduce such novels in our language that has not any partiality so that tradition of Urdu novel can adopt this angle. The Porcupine by Julian Barnes is such a novel which can show us how to treat the narration with impartiality and make the horizon of novel vaster and broader.